Health Technology Assessment of CD19 CAR T-Cell Therapies in the Irish Healthcare Setting. - Carey, Niamh Aisling (Trinity College Dublin. School of Medicine. Discipline of Pharmacology & Therapeutics, 2022)
The aim of this research was to undertake health technology assessments of CD19 CAR T-cell therapies, tisagenlecleucel and axicabtagene ciloleucel. A bespoke cost-utility model was developed to examine the cost effectiveness of tisagenlecleucel, versus blinatumomab, for relapsed/refractory acute lymphoblastic leukaemia (R/R ALL). Efficacy and utility inputs were derived by systematic literature review (SLR). Cost and resource use data were derived from Irish sources, where possible. To inform efficacy, two trials that investigated tisagenlecleucel and one that investigated blinatumomab were included in the evidence base. All were single-arm. Naïve comparison of overall survival (OS) indicated that tisagenlecleucel had favourable outcomes versus blinatumomab. However, this is uncertain. To address key areas of uncertainty in the evidence base of tisagenlecleucel, an expert elicitation was conducted. Areas of uncertainty examined included: the concept of cure and cure fraction, the proportion of patients expected to receive allogeneic stem cell transplant (alloSCT) following tisagenlecleucel, and the five-year OS of patients treated (i) with and (ii) without subsequent alloSCT. Much uncertainty was observed between judgements. Judgements were used to validate cost-utility model inputs and outputs. At the Irish willingness-to-pay threshold of 45,000 per QALY, tisagenlecleucel was not cost effective versus blinatumomab. The probability of cost effectiveness was 16%. Population expected value of perfect information (EVPI) and partial EVPI were low. Further research to decrease decision (parameter) uncertainty, at this payer threshold, is unlikely to be of value. Bespoke cost-utility models were also developed to examine the cost effectiveness of (i) tisagenlecleucel, and (ii) axicabtagene ciloleucel, for relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). Efficacy and utility inputs were derived by SLR. The utility of Abstrackr, a text-mining tool, in assisting in title and abstract screening of the SLR for efficacy data in R/R DLBCL. Cost and resource use data were derived from Irish sources, where possible. To inform efficacy, one trial each for tisagenlecleucel, axicabtagene ciloleucel, and salvage chemotherapy were included in the evidence base. All were single-arm. Clinical and methodological heterogeneity between the tisagenlecleucel and axicabtagene ciloleucel trials precluded a robust comparison. Naïve comparison of OS indicated that both tisagenlecleucel and axicabtagene ciloleucel had favourable outcomes versus salvage chemotherapy. However, this is uncertain. At a willingness-to-pay threshold of 45,000 per QALY, neither tisagenlecleucel nor axicabtagene ciloleucel were cost effective versus salvage chemotherapy. The probability of cost effectiveness (versus salvage chemotherapy) was 0% for tisagenlecleucel, and 1% for axicabtagene ciloleucel. Population EVPI and partial EVPI were low. The cumulative five-year gross drug budget impact, of tisagenlecleucel for R/R ALL, is 8.6 million (n=23 patients). Assuming a total of 120 patients, and a 50:50 market share, the cumulative five-year gross drug budget impact of tisagenlecleucel (n=60) and axicabtagene ciloleucel (n=60) is 45.6 million. These may be underestimated. Affordability of these therapies is a key challenge. Performance-linked reimbursement agreement scenarios were explored. Agreements, which captured outcomes over a longer time horizon, were impactful. However, affordability may remain a concern. Based on the inputs and assumptions used in this research, the reimbursement of CD19 CAR T-cell therapies is unlikely to represent cost-effective use of resources within the Irish healthcare setting. Performance-linked reimbursement agreements are necessary to reduce the associated financial risk.
APPROVED
Keywords: CAR T-Cell Therapy; Health Technology Assessment; Cost-Effectiveness Analysis; Value of Information Analysis; Performance-Linked Reimbursement